Response of grass species to different fire frequencies in semi-arid rangelands of central Argentina - Pelaez, Daniel V. (2013)
The study was undertaken to quantify the effect of different controlled fire frequencies on foliar cover, density, individual basal area, and mortality of the most common perennial grass species in the semi-arid rangelands of the southern Caldenal in central Argentina over a 20-year period. Cover of bare soil was also assessed. The study comprised three fire treatments: (i) high fire frequency (controlled burns every 3?5 years; HFF); (ii) low fire frequency (controlled burns every 8 years; LFF); and (iii) unburned control (C). Fire treatments, regardless of frequency, induced an increase in foliar cover and density in desirable grasses, no changes in intermediate grasses, and a decrease in undesirable grasses. Individual basal area tended to be higher for desirable grasses and lower for intermediate and undesirable grasses when subject to fire. Most of the species under study exhibited higher mortality rates in the HFF treatment than in the LFF andCtreatments. The results of the study suggest that recurrent controlled burns of moderate intensity may favour the herbage production of desirable perennial grasses. This, in turn, assuming appropriate grazing management, may have a beneficial impact on livestock production. Nevertheless, given the effects of fire on the cover of bare soil and mortality of grasses, further research is needed in order to determine the appropriate fire frequency in terms of rangeland sustainability.